â€œMATUR IBUâ€: ANALISIS BUDAYA DAN POLITIK DALAM PELAYANAN PUBLIK DI KABUPATEN KLATEN TAHUN 2018 - Nabella, Monica Amy; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2020)
Matur Ibu is an innovation program for public service complaints that was inaugurated by Sri Hartini (Regent of Klaten) and Sri Mulyani (Deputy Regent of Klaten). In the implementation of the complaints program, there was a problem because of the corruption case involved the Regent, Sri Hartini. After Sri Mulyani became the executor of the Klaten Regent's task, the Matur Ibu program became the main program and lead a new complaints program namely Sambang Warga. The using of Javanese language is closely related to the culture of the people in Klaten Regency with efforts to come to the community attempt by Sri Mulyani is considered by several parties to have a specific purpose to fulfill Sri Mulyani's personal interests.The purpose of this research is to analyze how the Matur Ibu program explains the political culture approach in the public service of the Klaten government. The various political efforts made by Sri Mulyani by riding on the Matur Ibu complaint program are very close to the culture that grows and is embedded in the lives of the people of Klaten. This research was conducted by using explorative qualitative method where primary data from this study were obtained directly from interviews with sources while secondary data is obtained indirectly through documents, mass media, internet and other literature studies. After choosing the method, the next step taken is to examine the data with data that has been obtained to draw the conclusions and verification. Based on these, it will produce a descriptive data to illustrate the results of the analysis of how the Matur Ibu program explains the approach of political culture in public services.According to data obtained from the results of field research, the word choice in Matur Ibu contains political elements. The word choice using Javanese language aims to form a social bond and affirm submission to Sri Mulyani. The approach strategy through the Sambang Warga program is carried out by Sri Mulyani form a positive image in the community as a good, protective, and solutive leader. The higher level of community participation mobilized will facilitate the transfer of corruption and political dynasties issues that have been inherent in the Klaten government and the figure of Sri Mulyani, so this will become a political investment which capable to facilitate Sri Mulyani's path to the Klaten District Head Election in 2020.Â Keywords: Matur Ibu program, Political Culture, Political Culture approach in Public Service